An ossifying bridge – on the structural continuity between the Achilles tendon and the plantar fascia - Johann Zwirner (Nature Portfolio, 2020)
Abstract Highly regular aligned trabeculae are found in the superficial posterior and inferior calcaneus appearing to connect the Achilles tendon (AT) to the plantar fascia (PF) in a bridge-like manner. This provides a morphological basis for the stretching-based heel pain treatment. However, the continuity of collagen fibres between the AT and the PF remains debated controversially to date. The given study morphologically investigated the AT-calcaneus-PF complex using histology and plastination. Moreover, the AT-calcaneus-PF complex was biomechanically mapped based on 13 sub-regions with a total of 76 tested samples. Regular calcaneal trabeculae were surrounded by tendon-like collagen fibre bundles and adipocytes. The orientation of calcaneal trabeculae was further closely related to the course of the PF collagen fibre bundles. The pooled biomechanical analysis revealed low elastic moduli (minimum = 4 MPa) and ultimate tensile strengths of the decalcified calcaneal samples (minimum = 0.4 MPa) and the calcaneal periostea (minimum = 2 MPa) and high respective values (elastic modulus maximum of 144 MPa; ultimate tensile strength maximum of 29 MPa) for the PF samples compared to the other sub-regions. This study provides structural evidence for a morphological connection between the AT and PF via the highly aligned calcaneal trabeculae of the posterior calcaneus. The AT-calcaneus-PF complex was biomechanically mapped to allow for an assessment of its site-dependent mechanical characteristics.